Ability Test of IAA (Indole-3-Acetic Acid) Hormone-Producing Endophytic Bacteria from Lamongan Mangrove - Fatimah, Fatimah; Lailatul Ayu Fadilah, Risky; Izzatul Millah, Annida; Nurhariyati, Tri; Irawan, Bambang; Affandi, Moch; Rini Nur Izza Zuhri, Afifa; Watamtin Widhiya, Eva; Salsabila, Syarifah; Asrifah Ramly, Zakia (Universitas Negeri Surabaya, 2022)
Most of the plant-associated bacteria can synthesize active biological components of phytohormones such as auxin. This study aimed to examine the potency of 61 endophytic bacteria isolates from the mangroves at Kutang Beach, Lamongan in producing IAA hormone and to identify types of isolates effecting the concentration of IAA, morphological characteristics of isolates, as well as endophytic bacterial species that have the most potential to produce IAA hormone. Screening of endophytic bacteria isolates was performed using the colorimetric method and the production of IAA was carried out using the spectrophotometric method. IAA production by endophytic bacteria was analyzed descriptively and statistically. One-Way ANOVA was employed to determine the effect of the isolate type on the concentration of IAA. The most potential isolates to produce IAA hormone are identified by 16s rRNA gene marker. The screening results showed that 12 isolates of endophytic bacteria have the potential to produce IAA hormones (2.0-9.3 ppm), coded with LMG 7, 15, 31, 32, 43, 53, 54, 55, 56, 57, 62, and 63. The results of the One-Way ANOVA test suggested that the type of isolates did not affect the concentration of IAA produced by endophytic bacteria. The twelve isolates had different morphological characters and those were Gram-positive bacilli with cell sizes ranging from 1.5 µm - 3 µm. The highest concentration of IAA was produced by LMG 15 (9.3 ppm). LMG 15 was identified as Bacillus cereus strain LMG 15, having 99.33% similarity to Bacillus cereus strain IAM 12605.